The MTNR1B Rs724030 variant is associated with islet function and women waist-to-hip ratio in healthy subjects - Zhang, Sijie; Bian, Wenxuan; Wang, Yan; Shen, Min; Qian, Yu; Dai, Hao; Zheng, Shuai; Fu, Qi; Xu, Kuanfeng; Yang, Tao; Jiang, Hemin (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the associations between MTNR1B rs724030 A>G variant and prediabetes risk, along with their correlations with clinical features, including plasma glucose and serum insulin levels during oral glucose tolerance test (OGTT), islet function, insulin resistance, and plasma lipid levels. In particular, we investigated whether there are sex dimorphisms in the impact of this variant on islet function/insulin resistance.MethodsWe included 3415 glucose-tolerant healthy and 1744 prediabetes individuals based on OGTT. Binary logistic regression was performed to evaluate the relationships between rs724030 in MTNR1B and prediabetes under the additive model. Additionally, multiple linear regression was utilized to investigate the associations between this variant and glycemic-related quantitative traits and lipid levels.ResultsWhile no association was observed between the rs724030 variant in MTNR1B and prediabetes risk in the overall cohort (P > 0.05), we found the G allele of this variant was associated with higher fasting and 30-minute plasma glucose levels, decreased Insulinogenic Index (IGI), and oral disposition index (DIo) (P = 0.009, 0.001, 0.001, and 0.007, respectively) in the normal glucose tolerance (NGT) individuals with normal BMI levels. Furthermore, we also found significant associations between this variant and IGI, corrected insulin response (CIR), and DIo (All P < 0.001) in female individuals whose waist-to-hip ratio (WHR) is greater than 0.85, with considerable heterogeneity (Phet = 0.009, 0.030, and 0.049, respectively) to male participants in the NGT individuals, but not in the impaired fasting glucose (IFG)/impaired glucose tolerance (IGT) individuals. Additionally, no association was observed between this variant and insulin clearance (All P > 0.05).ConclusionsThe MTNR1B rs724030 variant contributes to glycemic traits and islet function, and its effects have sex dimorphisms in the NGT individuals after stratifying by WHR. All these findings provide a basis for accurately assessing islet function in healthy populations and offer a new perspective on precision prevention.